2007
DOI: 10.1063/1.2713397
|View full text |Cite
|
Sign up to set email alerts
|

Rotational fluctuation of molecules in quantum clusters. II. Molecular rotation and superfluidity in OCS-doped helium-4 clusters

Abstract: In this paper, quantum fluctuations of a carbonyl sulfide molecule in helium-4 clusters are studied as a function of cluster size N in a small-to-large size regime ͑2 ഛ N ഛ 64͒. The molecular rotation of the dopant shows nonmonotonic size dependence in the range of 10ഛ N ഛ 20, reflecting the density distribution of the helium atoms around the molecule. The size dependence on the rotational constant shows a plateau for N ജ 20, which is larger than the experimental nanodroplet value. Superfluid response of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
(45 reference statements)
1
22
0
Order By: Relevance
“…Systematic analysis on the molecular rotational fluctuation of the OCS͑ 4 He͒ N is presented in the companion paper II. 12 In the following, we discuss the techniques developed in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systematic analysis on the molecular rotational fluctuation of the OCS͑ 4 He͒ N is presented in the companion paper II. 12 In the following, we discuss the techniques developed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…56 The small ͑but non-negligible͒ discrepancy between the present calculation and the experimental nanodroplet value will be discussed in the companion paper II. 12 In Fig. 4, we show a free-rotor correlation function using the estimated B eff .…”
Section: -7mentioning
confidence: 99%
“…It is important to note that the angulon quasiparticle theory described below is substantially simpler -and therefore more transparent -than numerical calculations based on Monte-Carlo algorithms [52,[54][55][56][57][58][69][70][71][72][73][74][75][76][77][78][79].…”
mentioning
confidence: 99%
“…The first similar study of a molecule (SF 6 ) with low resolution infrared spectrum was reported in 1992 [35], followed by its high resolution spectroscopic study in 1995 [4]; the term high resolution spectra refers to rotationally resolved microwave/ infrared spectra. In 1998, Grebenev et al analysed the spectra of a molecule, embedded in as few as 60 He atoms [5].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…represent the effects of quantum mechanics acting on the bulk properties of matter on a large scale and thus, superfluidity is, rightly, termed as macroscopic quantum phenomenon [1]. Recently, however, the high resolution spectroscopy of doped molecules in He nanodroplets (number of He atoms, N ~ 10 3 - 10 4 ) and clusters ( 4 He N -M, M being the embedded molecule and N = 1, 2, ...) [2] provided a unique method to explore superfluidity in such a microscopic system (MICROSCOPIC SUPERFLUIDITY [3]), as well [4][5][6]. It is found that the rotational spectrum of an embedded molecule in liquid He shows sharp peaks, similar to that of the molecule in gaseous state [5,7,8] which indicates that the molecule rotates like a free rotor, although, with an increased moment of inertia (I).…”
Section: Introductionmentioning
confidence: 99%